The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1029/2022gl099394
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Characterization of the Stratospheric Plume From the Volcanic Eruption at Hunga Tonga 15 January 2022

Abstract: The Hunga Tonga-Hunga Ha'apai (hereafter referred to as Hunga Tonga) volcano (20.57°S, 175.38°W) started an eruptive phase on 20 December 2021, with gas, steam and ash plumes periodically injected at around 12 km altitude. In mid-January larger eruptive events occurred on 13 and 15 January e.g., Yuen et al. (2022), Carr et al. (2022. The sub-aerial eruption on 13 January started at 15:20 UTC, injected plumes into the stratosphere that were observed at altitudes as high as 20 km, with an estimated sulfur dioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 46 publications
(73 reference statements)
3
26
0
Order By: Relevance
“…The two clouds C1 and C2 are well separated in altitude. A few days later, the Light Optical Aerosol Counter flight and ground lidar observations, both from La Réunion, confirm this by showing submicron size, mainly non-absorbing, particles (Kloss et al, 2022;Baron et al, 2022).…”
Section: Inferred Composition Of the Plumementioning
confidence: 73%
See 1 more Smart Citation
“…The two clouds C1 and C2 are well separated in altitude. A few days later, the Light Optical Aerosol Counter flight and ground lidar observations, both from La Réunion, confirm this by showing submicron size, mainly non-absorbing, particles (Kloss et al, 2022;Baron et al, 2022).…”
Section: Inferred Composition Of the Plumementioning
confidence: 73%
“…The extinction and backscatter coefficients have been estimated at 750 and 532 nm, respectively, to simulate OMPS and CALIOP observations. Typical sulfate aerosol refractive indices have been considered, with the assumption of very weakly absorbing particles (based on the results of Kloss et al, 2022). Lognormal size distributions with varying standard deviation are simulated, to study how this ratio changes with radius.…”
Section: Appendix A: Data and Methodsmentioning
confidence: 99%
“…Observations from IMS/IASI show that the plume is quickly transported westward over the Indian Ocean and a corresponding increase in fine mode AOD is observed from the ground at La Réunion island (Réunion Saint Denis and Maïdo OPAR AERONET stations, 20.9°S 55.5°E and 21.1°S 55.4°E, respectively) starting from 22nd January, with slightly reduced AODs (peak value ~0.6) due to plume dilution. A rapid-response balloon campaign was carried out at La Réunion to observe the young dispersed HT plume and to characterise its microphysical state 19 . In situ LOAC aerosol optical observations (see Methods) show enhanced aerosol extinction values at around 22 and 25 km altitude, composed of submicron, mainly liquid aerosol particles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For more details please refer to Ref. 19. In this work, we show LOAC measurement for 23 January 2022 (20-21:30 UTC).…”
Section: Methodsmentioning
confidence: 99%
“…These authors speculate that the high aerosol levels are not because of underestimated SO 2 emission, but due to accelerated conversion of SO 2 to sulfate aerosol because of the enhanced water vapor levels from the eruption, which is a known sensitivity (LeGrande et al., 2016). Several of these recent studies have also reported substantial increases in particle size from background levels, again likely due to the elevated water vapor, analyzing both spectral and depolarization characteristics of remote sensing satellite observations (e.g., Khaykin et al., 2022; Taha et al., 2022) as well as in situ sampling of the plume with balloon‐borne instrumentation (Kloss et al., 2022).…”
Section: Introductionmentioning
confidence: 99%